Knowledge of symptoms, time to presentation and barriers to medical help-seeking among Omani women diagnosed with breast cancer: a cross-sectional study. Issue 1 (21st January 2021) - Al-Azri, Mohammed; Al-Baimani, Khalid; Al-Awaisi, Huda; Al-Mandhari, Zahid; Al-Khamayasi, Jasem; Al-Lawati, Yaseen; Panchatcharam, Sathiya Murthi
Abstract : Objective: To identify knowledge of breast cancer (BC) symptoms, time taken to consult a doctor and factors contributing to delays in medical help-seeking. Design: A cross-sectional study of Omani women diagnosed with BC. Setting: The two main teaching hospitals in Oman: Royal Hospital and Sultan Qaboos University Hospital. Participants: Adult Omani women recently diagnosed with BC. Tools: The Breast Module of the Cancer Awareness Measure and the International Cancer Benchmarking Partnership questionnaire were used to collect data. Results: A total of 300 women with BC participated (response rate: 91.0%). The mean age at diagnosis was 43.0±12.50 years and 33.5% were diagnosed at stage III or IV. Although most women (74.4%) recognised breast/armpit lumps to be a symptom of BC, less than half identified other symptoms, including breast/armpit pain (44.0%), changes in the position of the nipple (36.2%), redness (31.7%), fatigue (26.3%), weight loss (23.4%) and loss of appetite (20.8%). While most (91.6%) were aware that BC could be cured if detected early, only 66.4% sought medical help within a month of developing symptoms. Initial responses to symptoms included informing husbands (40.2%) or family members (36.5%). Barriers to seeking medical help included feeling scared (68.9%) and worried about what the doctor might find (62.8%). Highly educated women were more likely to recognise the following as BC symptoms: changes in nipple position (OR: 0.16, 95% CI 0.03 to 0.81), breast pain (OR: 0.10, 95% CI 0.01 to 0.86) and unexplained weight loss (OR: 0.18, 95% CI 0.04 to 0.88) (all p<0.05). Conclusions: Although many Omani women with BC were aware of the importance of early diagnosis, most demonstrated inadequate knowledge of symptoms, did not prioritise seeking medical help and reported emotional barriers to help-seeking. More educational measures are needed to improve symptom recognition and address help-seeking barriers to minimise delays in diagnosis.